Immunogenicity, safety, and efficacy of the HPV vaccines among people living with HIV: A systematic review and meta-analysis. (October 2022) - Staadegaard, Lisa; Rönn, Minttu M.; Soni, Nirali; Bellerose, Meghan E.; Bloem, Paul; Brisson, Marc; Maheu-Giroux, Mathieu; Barnabas, Ruanne V.; Drolet, Melanie; Mayaud, Philippe; Dalal, Shona; Boily, Marie-Claude
Summary: Background: Vaccines have been demonstrated to protect against high-risk human papillomavirus infection (HPV), including HPV-16/18, and cervical lesions among HIV negative women. However, their efficacy remains uncertain for people living with HIV (PLHIV).We systematically reviewed available evidence on HPV vaccine on immunological, virological, or other biological outcomes in PLHIV. Methods: We searched five electronic databases (PubMed, Medline and Embase, clinicaltrials.gov and the WHO clinical trial database) for longitudinal prospective studies reporting immunogenicity, virological, cytological, histological, clinical or safety endpoints following prophylactic HPV vaccination among PLHIV. We included studies published by February 11th, 2021. We summarized results, assessed study quality, and conducted meta-analysis and subgroup analyses, where possible. Findings: We identified 43 publications stemming from 18 independent studies ( Ns =18), evaluating the quadrivalent ( Ns =15), bivalent ( Ns =4) and nonavalent ( Ns =1) vaccines. A high proportion seroconverted for the HPV vaccine types. Pooled proportion seropositive by 28 weeks following 3 doses with the bivalent, quadrivalent, and nonavalent vaccines were 0.99 (95% confidence interval: 0.95-1.00, Ns =1), 0.99 (0.98-1.00, Ns =9), and 1.00 (0.99-1.00, Ns =1) for HPV-16 and 0.99 (0.96-1.00, Ns =1), 0.94 (0.91-0.96, Ns =9), and 1.00 (0.99-1.00, Ns =1) for HPV-18, respectively. Seropositivity remained high among people who received 3 doses despite some declines in antibody titers and lower seropositivity over time, especially for HPV-18, for the quadrivalent than the bivalent vaccine, and for HIV positive than negative individuals. Seropositivity for HPV-18 at 29–99 weeks among PLHIV was 0.72 (0.66-0.79, Ns =8) and 0.96 (0.92-0.99, Ns =2) after 3 doses of the quadrivalent and bivalent vaccine, respectively and 0.94 (0.90-0.98, Ns =3) among HIV-negative historical controls. Evidence suggests that the seropositivity after vaccination declines over time but it can lasts at least 2–4 years. The vaccines were deemed safe among PLHIV with few serious adverse events. Evidence of HPV vaccine efficacy against acquisition of HPV infection and/or associated disease from the eight trials available was inconclusive due to the low quality. Interpretation: PLHIV have a robust and safe immune response to HPV vaccination. Antibody titers and seropositivity rates decline over time but remain high. The lack of a formal correlate of protection and efficacy results preclude definitive conclusions on the clinical benefits. Nevertheless, given the burden of HPV disease in PLHIV, although the protection may be shorter or less robust against HPV-18, the robust immune response suggests that PLHIV may benefit from receiving HPV vaccination after acquiring HIV. Better quality studies are needed to demonstrate the clinical efficacy among PLHIV. Funding: World Health Organization. MRC Centre for Global Infectious Disease Analysis, Canadian Institutes of Health Research, UK Medical Research Council (MRC).